Attitudes Towards Testing and Skills Required in Psychological Assessment - Baptista, Makilim Nunes; Junior, Natalício Augusto da Silva; Faiad, Cristiane; Cardoso, Hugo Ferrari [UNESP] (My University, 2022)
The development of attitudes towards testing and skills for good performance in the practice of Psychological Assessment (PA) is an important resource in the professional practice. This study investigated the attitudes, and competences of psychologists regarding PA. Study participants were 186 psychologists, from all regions of Brazil, who answered the Identification Questionnaire, the Psychologists' Attitudes towards Psychological Testing Questionnaire (QAPT) and the Competence for Psychological Assessment Questionnaire (QCAP). The results showed that the Competence Domain had the strongest relationship with several variables. Regression analysis demonstrated that the use of tests and postgraduate training were predictors of greater proficiency and having a Master's degree was a predictor of greater attribution to the importance of the skill. Therefore, investments in teaching and practice strategies can facilitate professional experience, fostering attitudes and skills necessary for quality practice.
Actitudes Hacia los Tests y Competencias Requeridas en la Evaluación Psicológica
Atitudes Frente à Testagem e Competências Requeridas na Avaliação Psicológica
Keywords: attitudes; knowledge; psychological assessment; skills